The Possibility of Identifying Alpha-Companies by Statistical Methods on the Example of the ExpressLogistics Market In Russia - V. A. Vertogradov (Мир новой экономики)
The article attempts to evaluate the use of the conventional statistical apparatus to identify alpha companies in the Russian express logistics market. According to the theory of economic dominance, Alpha-companies occupy dominant positions in industry markets due to access to the cheapest resources and institutional advantages that allow them to build barriers to other players. Identification of such companies has traditionally been carried out by an expert method, including based on insider information, not available to external market players. The author describes the traditional tools used to identify the dominant market players [concentration indices (CR), Lind (L) and Herfindahl-Hirschman (HHI)], made calculations based on official statistics, data from open ratings and other available benchmarks for the express delivery industry in Russia, as well as a comparison with the results of determining alpha companies by an expert method. The author formulated hypotheses to explain the reasons for situations when companies with dominant capabilities are not interested in realizing their potential in a small market. Additionally, the author used some assumptions about the role of institutions regulating the market in case of sharp changes in market conditions.